Applying team-based learning in a transnational post registration bachelor of nursing program in Singapore - Rob Burton; Thea van de Mortel; Victoria Kain (BMC, 2021)
Abstract Background Team-Based Learning (TBL) is growing in popularity as a method to create active learning within larger group lectures. It is facilitated through phases of individual work, teamwork with immediate feedback and an application exercise, to develop students' understanding and assessment of conceptual knowledge. A single facilitator can manage many groups within larger lectures. The study aim was to evaluate the impact of TBL on the engagement, learning and satisfaction of students enrolled in a transnational post registration Bachelor of Nursing (BN) program in Singapore. Methods A cross-sectional design was employed. The TBL approach was delivered during lecture sessions within a post registration BN program delivered in a Higher Education Institution in Singapore. A sample of BN students was drawn from 305 students undertaking the program. An online anonymous university-delivered student evaluation of course (SEC) survey and an online anonymous survey using the Student Assessment Instrument, were used to collect quantitative and qualitative data. Survey participation was voluntary with informed consent protocols followed. Student performance in the course was also reviewed. Results Eighty-two students (27%) completed the SEC scoring a median of 4/5 for satisfaction, and 68 (22%) completed the online survey. As 93 was the neutral score for the survey, there was a moderately positive evaluation with an overall score of 108.5/155 for TBL in accountability for learning, TBL preference and satisfaction with TBL compared to traditional lecture approaches. Conclusions Implementation of TBL with this cohort demonstrated evidence of moderately positive engagement, learning and satisfaction when compared to traditional didactic lectures.